Room temperature photoluminescence of individual self-assembled quantum dots - Zora, A.; Simserides, C.; Triberis, G.P. (Physica E: Low-Dimensional Systems and Nanostructures, 2008)
We investigate the emission spectra of individual lens-shaped self-assembled quantum dots (QDs) in the high-temperature regime in order to contribute to the fine structural analysis and to the appreciation of the QDs’ optical response. Our theoretical analysis results in an expression for the photoluminescence (PL) intensity of QDs in the linear regime, which reproduces satisfactorily the experimentally observed PL signal of individual lens-shaped In0.5Ga0.5As self-assembled QDs. Using the appropriate material parameters, the theoretical predictions for the interlevel spacing as well as for the dephasing time caused by electron-longitudinal optical phonon interactions are in good agreement with experiment.